Safety Culture Assessment: a Tool for Improving Patient Safety in Hospital - Dewi Agustina (Universitas Muhammadiyah Yogyakarta, 2018)
The patient safety culture at the ‘X’ Hospital Palembang is still not good enough as can be seen from the number of reported patient safety incidents from KPRS team. Meanwhile, this C-type hospital is obligated to implement patient safety culture in improving health service quality. This research uses the quantitative method with a cross-sectional approach. The research samples are taken using Slovin’s formula from medic and paramedic, medical support, and management and sampling with proportional stratified random sampling. Measurement of patient safety culture uses MaPSaF (Manchester Patient Safety Framework) questionnaire which has been published by NPSA (National Patient Safety Agency) in 2006 and has been tested for its validity and reliability by previous research. The questionnaire consists of 10 dimensions with 24 aspects of the question. The implementation of the patient safety culture at the ‘X’ Hospital Palembang has been in accordance with MaPSaF assessment of 70% at the proactive level, 20% at the generative level, and also 10% at the bureaucratic level. Overall, the patient safety culture is dominant at the proactive level, yet improvement is still needed to the generative level by raising awareness, good cooperation, and responsibility for the importance of patient safety culture.